Potensi Antioksidan Ekstrak Metanol Fuli Pala (Myristica fragrans Houtt) - Djamaluddin, Rosmiyati R; Putra Pratama, Nofran; Nurhasanah, Devika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background : The mace is the part that surrounds the nutmeg seeds. Mace and nutmeg seeds are widely used as a spice in food products and in traditional medicine used as a remedy for stomach pain, analgesics, stimulants. Nutmeg mace also contains flavonoids and phenolics that have potential as antioxidants. Research Objective: Determine the antioxidant activity of methanol extract of nutmeg mace (Myristica fragrans Houtt) in reducing free radicals DPPH Research Method: Nutmeg macaques are extracted using methanol solvents through a maceration process (1:10), then the extracts obtained are tested, namely organoleptic tests, moisture content tests, phytochemical tests, KLT tests, and antioxidant tests using quercetin comparators with varying concentrations, namely 2 ppm, 4 pmm, 6 ppm, 8 ppm, and 10 ppm Research Results: The results of the organoleptis test showed that the methanol extract of nutmeg mace had a deep black color, a distinctive aroma, and a thick texture. 0.83% for moisture content test results. The results of phytochemical screening showed that nutmeg mace methanol extract was positive for flavonoids, phenolics, alkaloids, saponins, and tannins. The KLT test also showed positive results containing flavonoids. The free radical scavenging activity of DPPH from metanol extract of nutmeg mace showed an IC50 value of 13.781 ppm ±SD 0.247 and a standard IC50 value of 4.181 ppm ±SD 0.247 compared to quercetin. Based on statistical analysis, there was no significant difference because the data obtained was 0.074 > 0.05 Conclusion: Methanol extract of nutmeg mace has antioxidant activity in reducing DPPH free radicals and shows an IC50 value of 13.781 ±0,211 ppm which is included in the category of very strong.